Development of Comprehensive Risk Management Framework for Sustainable Solar Mini-Grid Project Implementation in Zambia - Sabita Thapa; Balimu Mwiya; Mabvuto Mwanza (CV FOUNDAE, 2025)
Solar mini-grids present a viable solution for electrifying off-grid rural and remote areas. However, their implementation and long-term sustainability encounter several challenges in most developing countries, including Zambia. This study aims to identify the risks associated with solar mini-grids in Zambia and to explore effective mitigation strategies. By adopting ISO 31000 for risk management, the research develops a comprehensive Risk Management Framework tailored to the needs of solar mini-grid projects. An inductive approach is used to investigate the key risks affecting the faster adoption and deployment of solar mini-grids in Zambia, allowing for an in-depth exploration and understanding of complex phenomena. Expert interviews serve as the primary data collection method, providing detailed insights from individuals experienced in solar mini-grid projects in Zambia. The data gathered through these interviews is analyzed using MAXDQA software, a tool for qualitative data analysis. The findings reveal a lack of a standardized and comprehensive risk management framework, with organizations relying on isolated tools such as risk registers and assessment matrices, leading to inefficiencies and sustainability challenges. Key risks identified include funding difficulties, licensing issues, technology acceptability issues, energy affordability, and system design failures leading to technical issues. The study proposes several mitigation strategies, including diversifying funding sources, streamlining regulatory processes, implementing training programs, engaging local communities, and ensuring high-quality procurement. It is recommended that a comprehensive, integrated risk management framework be established, incorporating continuous risk monitoring throughout the project lifecycle. Additionally, the research highlights the importance of capacity-building initiatives, stakeholder engagement, sustainable business models, and post-project monitoring to ensure the long-term success and resilience of solar mini-grids in Zambia.